Acute lower limb ischemia caused by vaccine-induced immune thrombotic thrombocytopenia: focus on perioperative considerations for 2 cases - Guillaume Roberge; Benoit Côté; Anthony Calabrino; Nathalie Gilbert; Nathalie Gagnon (Thrombosis Journal, 2022)
Abstract Background ChAdOx1 nCoV-19 (AstraZeneca) and Ad26COV2.S (Johnson & Johnson/Janssen) adenoviral vector vaccines have been associated with vaccine-induced immune thrombotic thrombocytopenia (VITT). Arterial thrombosis and acute limb ischemia have been described in a minority of patients with VITT. These patients usually need a revascularization, but they potentially are at a higher risk of complications. Optimal perioperative care of patients undergoing vascular surgery in acute VITT is unknown and important considerations in such context need to be described. Cases presentations We report 2 cases of VITT presenting with acute limb ischemia who needed vascular surgery and we describe the multidisciplinary team decisions for specific treatment surrounding the interventions. Both patients’ platelet counts initially increased after either intravenous immune globulin (IVIG) or therapeutic plasma exchange (TPE). None received platelet transfusion. They both received argatroban as an alternative to heparin for their surgery. Despite persistent positivity of anti-platelet factor 4 (PF4) antibodies and serotonin-release assay with added PF4 (PF4-SRA) in both patients, only one received a repeated dose of IVIG before the intervention. Per- and post-operative courses were both unremarkable. Conclusion In spite of persistent anti-PF4 and PF4-SRA positivity in the setting of VITT, after platelet count improvement using either IVIG or TPE, vascular interventions using argatroban can show favorable courses. Use of repeated IVIG or TPE before such interventions still needs to be defined.